The Quality of Dry Noodle With Substitution of Suji Leaves Extract (Kualitas Mie Kering dengan Substitusi Ekstrak Daun Suji) - Safitri, Elsa Nur; Mustika, Sari; Faridah, Anni; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
Suji leaves have many health benefits, namely as a high source of antioxidants because the contain chlorophyll, flavonoids and saponins in them. However, the use of suji leaves itself is still not optimal even though the amount is very abundant and tends to be easy to cultivate. The use of suji leaf extract is expected to use as well as a natural coloring agent with green pigments in functional food products, so that it can replace the use of synthetic dyes which can be harmful to health when used excessively and for a long time. This study aims to analyze the effect of suji leaves extract substitution of 0% (X0), 60% (X1), 80% (X2), and 100% (X3) on the dry noodles quality in terms of shape, color, aroma, texture and taste. The type of research used was a pure experiment using a completely randomized design (CRD). The data used is data obtained directly from 3 limited panelists by filling out the organoleptic test form on the quality of suji leaves extract dry noodles. The data that has been obtained is then tabulated in tabular form and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount > Ftable then proceed with Duncan's test. The results showed that there was a significant substitution effect of suji leave extract between 60%, 80% and 100% on the quality of color (green) and aroma (suji leaf) in dry noodles. Meanwhile, there was no significant effect on the quality of shape (square shaped and uniform width of 1.5 mm), texture (dry), texture (springy), texture (not easily broken) and taste (savory) in dry noodles. The best quality test results for dried noodles with suji leaf extract were in treatment X3 with 100% using of suji leaf extract.